PENYIMPANGAN MORAL SISWA: STUDI KASUS DI SMPN 2 KEDIRI, LOMBOK BARAT - Baik Halimatussakdiah; Lalu Sumardi; Muhammad Zubair (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2022)
The purpose of this study was to identify the factors that cause students' moral deviations and to know the role of schools and parents in overcoming students' moral deviations. The research uses a naturalistic approach with a case study type. The informants of this study were parents, teachers, chief of school, and students of SMPN 2 Kediri. Data was collected using observation, interview, and documentation techniques. Data analysis was carried out using the interactive model proposed by Miles, Huberman, and Saldana with three steps, namely: data reduction, data presentation, and drawing conclusions. This study found three factors that cause students' moral deviation, namely: 1) family factors; consisting of parents' education and family economic conditions; 2) social environmental factors; consists of the community environment where they live and playmates. Regarding the role of schools and families in overcoming students' moral deviations, it was found that schools have a major role in preventing and overcoming students' moral deviations. Meanwhile, the family is the opposite.